1985
DOI: 10.1530/jrf.0.0730197
|View full text |Cite
|
Sign up to set email alerts
|

The presence of glucose increases the lethal effect of  -chlorohydrin on ram and boar spermatozoa in vitro

Abstract: Ram cauda epididymal spermatozoa were incubated for 10 min at 34 degrees C with or without 1.0 mM-RS-alpha-chlorohydrin before (1) 5 mM-D-glucose or (2) 10 mM-L-lactate plus 1 mM pyruvate or (3) 5 mM-D-glucose plus 10 mM-L-lactate plus 1 mM-pyruvate or (4) no substrate was added. Without alpha-chlorohydrin, the motility, the ATP concentration and the energy charge of the spermatozoa were maintained for 240 min by substrate combinations 1-3 but with no added substrate (4) the motility declined after 60 min. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…When BHB was supplemented to the sperm suspension instead of glucose, the percentage of sperm motility was not affected by α-chlorohydrin (ACH), a potent inhibitor of GAPDH. Moreover, it was reported that intracellular ATP concentration was not decreased by ACH in the absence of glucose (Ford and Harrison, 1985;Ford and Harrison, 1986). These results support that respiration is enough to supply ATP for sperm motility.…”
Section: Introductionsupporting
confidence: 66%
“…When BHB was supplemented to the sperm suspension instead of glucose, the percentage of sperm motility was not affected by α-chlorohydrin (ACH), a potent inhibitor of GAPDH. Moreover, it was reported that intracellular ATP concentration was not decreased by ACH in the absence of glucose (Ford and Harrison, 1985;Ford and Harrison, 1986). These results support that respiration is enough to supply ATP for sperm motility.…”
Section: Introductionsupporting
confidence: 66%
“…Rat sperm treated with this compound remained motile and maintained normal ATP content with pyruvate plus lactate as energy substrate in the absence of glucose (Ford and Harrison, 1981). Epididymal ram sperm and ejaculated boar sperm, treated with chlorhydrin, in a like manner maintained motility for 60 min with pyruvate plus lactate as energy substrates in the absence of glucose, but addition of glucose rapidly diminished motility in the presence of these substrates, and did not sustain motility as sole substrate (Ford and Harrison, 1985). The implication of these experiments, of the experiments of Mukai and Okuno (2004), and of the experiments with gapds -/-mice (Miki et al, 2004) is that glucose acts as a metabolic poison, akin to 2-deoxyglucose, when GAPD-S in sperm is knocked out or its activity blocked by inhibitor.…”
Section: Glycolysis and Motility: Sugar As Friendmentioning
confidence: 94%
“…Their mode of action probably relies on the inhibition of glyceraldehyde 3-phosphate dehydrogenase (EC 1.2.1.12) in spermatozoa which blocks the glycolytic pathway in these cells (Brown-Woodman, Mohri, Mohri, Suter & White, 1978;see Ford, 1982). Ford & Harrison (1985) have demonstrated that a-chlorohydrin has relatively little effect on the energy balance of spermatozoa unless glucose is added, when the concentration of ATP in the cells decreases dramatically. In the present study the conditions required for glucose-dependent ATP dissipation to occur have been investigated further and the phenomenon has been correlated with changes in the concentrations of glycolytic intermediates.…”
Section: Introductionmentioning
confidence: 99%